Soil nitrogen dynamics in natural forest ecosystem: a review - Sardar, Muhammad Fahad; Younas, Fazila; Farooqi, Zia Ur Rahman; Li, Yanli (Frontiers in Forests and Global Change, 2023)
Nitrogen (N) is an important component of the forest soils and plays a pivotal role in the ecosystem’s health, also in broadleaf and Moso bamboo (Phyllostachys edulis) forests. Nitrogen plays numerous functions in the production and transformation of soil organic matter (SOM) and alterations in the soil’s physicochemical and biological properties. Despite the extensive research on soil properties and microorganism diversity in broadleaf and Moso bamboo forests, we still know very little about N dynamics and its significance in broadleaf and Moso bamboo forests, or how various physical and environmental variables influence soil physicochemical, N dynamics, and biological attributes. This article provides a thorough overview of the role of N dynamics in broadleaf and Moso bamboo forests and changes in soil physicochemical properties processes by summarizing recent advances in our knowledge of forest soil microbial diversity, and carbon (C) and N sink in broadleaf and Moso bamboo forests. As broadleaf and Moso bamboo forests are very sensitive to little change, even a small change in these ecosystems can alter the overall N dynamics. Here, we dissect the soil ecology of broadleaf and Moso bamboo forests to provide insights into the possibilities and consequences of future studies of N dynamics in these ecosystems.